«The Admiral is becoming a dangerous ward for us» French General M. Janen’s assessment of situation on the White Eastern Front in December 1918 - R. G. Gagkuev (Омский научный вестник: Серия "Общество. История. Современность")
The publication tells about the beginning of the activities in Siberia of the French General M. Janin, who arrived in the Far East in November 1918 as a representative of the Entente command and the future commander-in-chief of all the troops of the anti-Bolshevik Eastern Front. The situation in which the head of the French military mission in Siberia found himself in November-December 1918, his vision of the conflict between the Supreme Ruler Admiral A. V. Kolchak and Ataman G. M. Semenov, the role of the Czechoslovak Corps in the events of 1918, positions Japanese Expeditionary Force. The most important part of the work is Janin’s first published report to the French Minister of War. It describes in detail the conflict between A. V. Kolchak and G. M. Semenov, gives an assessment of Kolchak himself. The publication is addressed to researchers of the military-political sphere and international relations during the Civil War in Russia.